ANALISIS KOMPETENSI GURU DI SDN GIRIMOYO 2 KABUPATEN MALANG - Kuncahyono, Kuncahyono (Jurnal Ilmiah Sekolah Dasar, 2017)
The purpose of this research is to know the teacher competence in elementary school of Girimoyo 2 Malang. The research method used in this case is qualitative type, with descriptive approach and done in this step is data analysis taken from interview perspective, this data analysis start from data reduction, data of choice, to conclusion, and data of this instrument taken from interview guide and observation of teachers in the elementary school. The results of this study resulted in 2 findings 1) Competence of teachers after getting educator certificate: able to carry out learning with professional (pedagogic competence, professional, personality, social) and very professional in developing media because of the allowance of teachers.2) competence of teachers who are getting educator certificate : able with good planning, implementation and evaluation, although there is no teacher allowance, business teacher as much as possible for artificial media